The impact of 2 years of additional athletic training on the jump performance of young athletes - Keiner, M.; Sander, A.; Wirth, K.; Schmidtbleicher, D. (Science & Sports, 2014)
Objectives: An early-established strength training regimen brings many benefit young athletes, especially those engaged in competitive sports. Strength training also leads to improve athletic performance, strength training is used for rehabilitation and injury prevention. The aim of this study was to evaluate how 2 years of additional strength training and plyometric training in elite 9- to 12-year-old soccer players (n = 70) affects their performance in the squat jump (SJ), countermovement jump (CMJ) and drop jump (DJ). Equipment and methods: Therefore, subjects were divided into two groups. The difference between the first group (CG = soccer) and the second group (STG) was the additional strength training (1 to 2times per week) and athletic units for the second group (STG = soccer and strength and plyometric training). For the analysis, performance gains within a group and for pair-wise comparisons between 2groups, analysis of variance was performed with repeated measures with group and time factors. Results: The results show in most variables a significant (P < 0.05) positive effect on performance in the SJ, CMJ and DJ tests for both groups over the time. The results also show in most variables significant (P < 0.05) better performances in the STG compared to the CG. Conclusion: Therefore, long-term resistance training is recommended as early as childhood and adolescence.